Validation of the pectoralis minor length test: A novel approach. (April 2016) - Weber, Christian; Enzler, Marcel; Wieser, Karl; Swanenburg, Jaap
Abstract: Introduction: Pectoralis minor (PM) shortness is believed to promote faulty shoulder mechanics including reduced scapular posterior tilt. A pectoralis minor length (PML) test that measures the acromion-table distance with and without manual pressure on the coracoid process is supposed to examine the passive mechanical properties of the PM. A threshold for "shortening" has been set at 2.6 cm, but data regarding its validity are lacking. We hypothesized that, under conditions of good reliability, an evaluation of the effect of PM tenotomy, could adequately investigate the construct validity of this test. Methods: Sixteen subjects with anterior shoulder instability who were undergoing open Latarjet procedures were recruited. We performed the PML test with and without pressure (1) in a clinical setting to check for intratester reliability and setting comparability and (2) in an intraoperative setting immediately before and after PM tenotomy to assess the construct validity. Results: The PML test exhibited excellent intra-tester reliability (intracorrelation coefficients, ICC > 0.94) and reasonable setting comparability (ICC 0.31–0.54). The change following intraoperative PM tenotomy was significant (p < .008) but small (mean = 0.46–0.50 cm) compared to the measurement variability (standard deviation 1.0–1.5 cm). In 12 of the 16 subjects, the measurements remained above the threshold of 2.6 cm. Conclusions: The influence of the PM on the PML test seems to be minor compared to other factors that cause high measurement variability. A threshold of 2.6 cm cannot distinguish between short and normal PMs. Our findings suggest that the impact of the PM on restricted scapular posterior tilt might be smaller than believed. Highlights: We investigated the immediate effect of tenotomy on the pectoralis minor length test. The influence of the pectoralis minor on the test results seems to be small (8–13%). A recommended threshold of 2.6 cm is not useful to detect pectoralis minor shortness. The pectoralis minor seems to just slightly restrict scapular posterior tilt.